The Canada Goose in Florida - Adam S. Willcox; William M. Giuliano (EDIS, 2006)
WEC-211, a 4-page illustrated fact sheet by Adam S. Willcox and William M. Giuliano, provides information on identification and biology, food and nesting habitat, distribution and migration, conservation, and control of these large protected migratory birds. Includes references for further information. Published by the UF Department of Wildlife Ecology and Conservation, May 2006.